The features of stress field in the Javakheti volcanic highland determined by the earthquake focal mechanisms for the time period 2005-2017 - E. E. Sahakyan (ՀՀ ԳԱԱ հրատ.)
The Javakheti Volcanic Highland, located in the central Caucasus, is part of the Arabia-Eurasia continental collision zone. This area is characterized by increased seismic activity and volcanism where earthquake distribution is diffuse. In this study, source mechanisms of earthquakes using digital waveform data recorded by seismic stations of the Armenian, Georgian, and adjacent seismic networks have been investigated. The focal mechanisms of a set of earthquakes that occurred within 2005– 2017 with high reliability, based on the polarity of the first motion of the P-wave have been constructed. The azimuth, angle of incidence, and polarities of the P-phase were used to obtain initial focal mechanism solutions. A re-location for selected seismic events during this time period was also performed. Աշխատանքում իրականացվել է Ջավախքի հրաբխային բարձրավանդակում 2005-2017 թթA ընթացքում գրանցված երկրաշարժերի ֆոկալ մեխանիզմների հաշվարկ։ Օգտագործվել են Հայաստանի, Վրաստանի, ինչպես նաև հարակից մյուս սեյսմիկ կայանների կողմից գրանցված երկրաշարժերի թվային ալիքային պատկերները։ Ֆոկալ մեխանիզմները հաշվարկվել են P ալիքի առաջին մուտքի նշանի մեթոդի կիրառմամբ։ Լուծումները տրվել են P ալիքի բևեռացման, սեյսմիկ կայանի նկատմամբ ազիմուտային անկյան, ինչպես նաև ալիքի անկման անկյան տվյալների հիման վրա։ Այն երկրաշարժերը, որոնց համար հաշվարկվել են ֆոկալ մեխանիզմները, իրականացվել է նաև էպիկենտրոնների և հիպոկենտրոնների վերահաշվարկ (re-location): Джавахетское вулканическое нагорье, расположенное на Центральном Кавказе, является частью зоны континентальной коллизии Аравии и Евразии. Эта область характеризуется повышенной сейсмической активностью и вулканизмом, где распределение землетрясений рассеянное.В данном исследовании мы изучаем механизмы очагов землетрясений с использованием цифровых волновых данных, зарегистрированных сейсмическими станциями армянской, грузинской и смежных с ними сейсмических сетей. Мы строим фокальные механизмы для группы землетрясений, произошедших в период 2005–2017гг, с большим уровнем надежности, на основе полярности первого вступления P-волны. Для получения первоначальных решений фокальных механизмов использовались азимут, угол наклона и полярности P-фазы.
Keywords: Science; Geology; Seismology; Volcanology